Comparison of two approaches in achieving smoking abstinence among patients in an outpatient clinic: A Phase 2 randomized controlled trial. Issue 5 (May 2018) - Ho, K.Y.; Li, William H.C.; Wang, M.P.; Lam, K.K.W.; Lam, T.H.; Chan, Sophia S.C.
Highlights: Abrupt quitting was more effective than cutting down to quit at 6- but not 12-month. Cutting down to quit was a more demanding intervention for patients. Feasibility needs reassessment if intervention is intensified to improve efficacy. Effectiveness of various approaches in achieving abstinence should be studied. Abstract: Objectives: To compare the effectiveness of quitting immediately and cutting down to quit in promoting smoking abstinence among smokers in an outpatient clinic. Methods: A total of 100 subjects were randomized into two groups, 50 in the quit immediately group, who received an intervention on abruptly quitting, and 50 in the cut down to quit group, who received an intervention on gradual reduction. All subjects were followed up at 6 and 12 months via telephone. The intention-to-treat principle was used. Results: At the 6-month follow-up, the self-reported quit rate of subjects in the quit immediately group was significantly higher than in the cut down to quit group (18.0% vs. 4.0%, p = 0.04). However, this difference was not significant at the 12-month follow-up (12.0% vs. 4.0%, p = 0.16). Conclusion: These data suggest that quitting immediately might be more effective than cutting down to quit at 6 months but not at 12 months. Practice implications: It is crucial to allow smokers to select quitting immediately or reducing the number of cigarettes smoked. Further studies are warranted to compare the effectiveness of various approaches for achieving smoking abstinence.